Reduced G protein signaling despite impaired internalization and β-arrestin recruitment in patients carrying a CXCR4Leu317fsX3 mutation causing WHIM syndrome - Rajesh Kumar; Samantha Milanesi; Martyna Szpakowska; Laura Dotta; Dario Di Silvestre; Anna Maria Trotta; Anna Maria Bello; Mauro Giacomelli; Manuela Benedito; Joana Azevedo; Alexandra Pereira; Emilia Cortesao; et al. (JCI Insight, 2023)
WHIM syndrome is an inherited immune disorder caused by an autosomal dominant heterozygous mutation in CXCR4. The disease is characterized by neutropenia/leukopenia (secondary to retention of mature neutrophils in bone marrow), recurrent bacterial infections, treatment-refractory warts, and hypogammaglobulinemia. All mutations reported in WHIM patients lead to the truncations in the C-terminal domain of CXCR4, R334X being the most frequent. This defect prevents receptor internalization and enhances both calcium mobilization and ERK phosphorylation, resulting in increased chemotaxis in response to the unique ligand CXCL12. Here, we describe 3 patients presenting neutropenia and myelokathexis, but normal lymphocyte count and immunoglobulin levels, carrying what we believe to be a novel Leu317fsX3 mutation in CXCR4, leading to a complete truncation of its intracellular tail. The analysis of the L317fsX3 mutation in cells derived from patients and in vitro cellular models reveals unique signaling features in comparison with R334X mutation. The L317fsX3 mutation impairs CXCR4 downregulation and β-arrestin recruitment in response to CXCL12 and reduces other signaling events — including ERK1/2 phosphorylation, calcium mobilization, and chemotaxis — all processes that are typically enhanced in cells carrying the R334X mutation. Our findings suggest that, overall, the L317fsX3 mutation may be causative of a form of WHIM syndrome not associated with an augmented CXCR4 response to CXCL12.